A randomized controlled trial of homeopathic treatment of weaned piglets in a commercial swine herd - Soto, F. R. M.; Vuaden, E. R.; Coelho, C. dP; Benites, N. R.; Bonamin, L. V. [UNESP]; de Azevedo, S. S. (Elsevier B.V., 2008)
Aim: To evaluate the zootechnic performance and occurrence of diarrhea in piglets in the week post-weaning comparing supplementation with sucrose saline which contained or did not contain added homeopathic medicine.Method. Animals were randomly divided into three groups of 24 piglets each. The control group did not receive any treatment. Another group received sucrose saline, and the third group received sucrose saline with homeopathic medicine added, in the period of zero to seven days post-weaning. The homeopathic treatment consisted of Echinacea angustifolia, Avena sativa, Ignatia amara, Calcarea carbonica, all 6cH. Piglets were weighed daily for weight gain or loss, and observed for diarrhea and feed intake.Results: Animals receiving sucrose saline alone and sucrose saline with homeopathy had less weight loss than control (p = 0.017, p = 0.0001 respectively). There was no statistical difference in relation to overall incidence of diarrhea or food consumption. These data suggest that the supplementation with sucrose saline with added homeopathic medicine in the first seven days post-weaning may be an useful option to reduce weight loss in weaned piglets. Homeopathy (2008) 97, 202-205.
Keywords: piglets; weaning; sucrose saline; homeopathy